Physicochemical and aromatic composition of ‘Sauvignon Blanc’ wines obtained from the Y-trellis and VSP training systems Composição físico-química e aromática de vinho ’Sauvignon Blanc’ obtido dos sistemas de sustentação Y e espaldeira - Filho J.L.M. (2021)
© 2021. All Rights Reserved.The objective of this work was to compare the effect of the Y-trellis and vertical shoot position trellis (VSP) training systems on the physicochemical composition and aromatic profile of ‘Sauvignon Blanc’ (Vitis vinifera) wines in a high-altitude region of the state of Santa Catarina, Southern Brazil. The experiment was conducted during the 2015 vintage in a commercial vineyard located in the municipality of São Joaquim. The treatments consisted of the training systems: Y-trellis and VSP pruned in spur cordon. Sixty kilograms of grapes were harvested from each training system to make the wines, which were evaluated as to their chemical and phenolic composition and aromatic profile. There is no effect of the training system on the wine chemical variables pH, total acidity, color, and total polyphenols. The aromatic profile and phenolic composition of the wines are affected by the training systems, being related to the variables ethyl acetate, isoamyl acetate, 3-methyl-1-butanol, propanoic acid, and gallic acid in the Y-trellis, and to 1-hexanol, isovaleric acid, caprylic acid, capric acid, and catechin in VSP. The Y-trellis system can be an alternative for high-altitude regions of Southern Brazil.